The Cursillo movement in America catholics, protestants, and fourth-day spirituality - Nabhan-Warren, Kristy (Chapel Hill, North Carolina : The University of North Carolina Press, 2013)
"The internationally growing Cursillo movement, or "short course in Christianity," founded in 1944 by Spanish Catholic lay practitioners, has become popular among American Catholics and Protestants alike. This lay-led weekend experience helps participants recommit to and live their faith. Emphasizing how American Christians have privileged the individual religious experience and downplayed denominational and theological differences in favor of a common identity as renewed people of faith, Kristy Nabhan-Warren focuses on cursillistas--those who have completed a Cursillo weekend--to show how their experiences are a touchstone for understanding these trends in post-1960s American Christianity"--
"The internationally growing Cursillo movement, or "short course in Christianity," founded in 1944 by Spanish Catholic lay practitioners, has become popular among American Catholics and Protestants alike. This lay-led weekend experience helps participants recommit to and live their faith. Emphasizing how American Christians have privileged the individual religious experience and downplayed denominational and theological differences in favor of a common identity as renewed people of faith, Kristy Nabhan-Warren focuses on cursillistas--those who have completed a Cursillo weekend--to show how their experiences are a touchstone for understanding these trends in post-1960s American Christianity. Drawing on extensive ethnographic fieldwork as well as historical research, Nabhan-Warren shows the importance of Latino Catholics in the spread of the Cursillo movement. Cursillistas' stories, she argues, guide us toward a new understanding of contemporary Christian identities, inside and outside U.S. borders, and of the importance of globalizing American religious boundaries"--
Cover Page; The Cursillo Movement in America; Copyright Page; Dedication; Contents; Illustrations; Preface New Beginnings; Introduction Finding Christ and Community in America; Chapter One Los Orígenes Mallorquines; Chapter Two Coming to America; Chapter Three A Focus on Christian Experience; Chapter Four Blooming Where We're Planted; Chapter Five Teens Encounter Christ; Chapter Six Feeding Bodies and Souls; Chapter Seven Maverick yet Mainstream; Epilogue Cursillo Weekends, Fourth-Day Spirituality, and the Future; Appendix One Cursillo Chronology; Appendix Two Glossary; Notes; Index.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Cursillo Movement in the United States; United States -- Church history -- 20th century; Cursillo Movement in the United States; United States; RELIGION / Christianity / Catholic; HISTORY / United States / 20th Century; Cursillo Movement in the United States; Lay ministry; Prayer; Spiritual retreats -- Catholic Church -- Education; Spiritual retreats; RELIGION / Christian Life / Spiritual Growth; 1900 - 1999; Church history; Electronic books